The temperature dependence of photo-elastic properties of cross-linked amorphous polyethylenes - Saunders, D. W.; Parsons, D. A.; Lightfoot, D. R. (College of Aeronautics, 1967)
Cross-linked samples of polyethylene were prepared by electron irradiation of both high and low density polymers in the crystalline state. A further cross-linked sample was obtained by curing a high density polyethylene by reaction with dicumyl peroxide at 180°C. The stress-strain birefringence relations were obtained, on specimens cut from these samples, at temperatures between 130 and 250°C. All samples showed a substantial decrease in stress-optical coefficient with increasing degree of cross-linking and with increasing temperature. The stress-optical properties at each temperature were extrapolated to zero degree of cross-linking to give quantities characteristic of the Guassian network. Comparison of these properties with Gaussian theory of the network leads to a value of ca.1150 cals/mole for the difference in energy between trans and gauche conformations of successive links of the polyethylene chain and also indicates that the optical anisotropy of a - CH2 group in the elastomeric state is more nearly given by Denbigh’s than by Bunn and Daubeny's polaris-abilities.